Religion of Democracy - Peden, W. Creighton (Newcastle-upon-Tyne : Cambridge Scholars Publishing, 2014)
This volume concludes Dr Peden's series on the empirical tradition in American Philosophical and Religious Thought.
Intro -- TABLE OF CONTENTS -- PREFACE -- HISTORICAL SKETCH -- FIRST DECADE -- THE WRITINGS -- THE FIRST WINDUP -- SECOND DECADE -- THE WRITINGS -- THE SECOND WINDUP -- THIRD DECADE -- THE WRITINGS -- THE THIRD WINDUP -- FINALE -- NOTES -- PUBLICATIONS FROM THEEMPIRICAL PROJECT -- BIBLIOGRAPHY -- INDEX.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2024. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Smith, Gerald Birney, -- 1868-1929.; Christian sociology -- History; Religion and politics -- History; Electronic books